Digital education and the future of ways to teach and learn - Muñoz Organero, Mario (Avances en Supervisión Educativa, 2013)
This article presents some brushstrokes of a couple of technological elements that are producing great transformations in the educational environment and that, undoubtedly, will continue to do so in the near future as an approach to the subject of this digital education of the future: the MOOCs and the use of mobile devices.MOOCs or massive online and open courses (Massive Open On-line Courses in English) open the knowledge of traditional closed courses that have been used for the transmission of knowledge.For its part, mobile devices, increasingly present in all the scenarios of our lives and how could it be otherwise in education, add new components to the educational process at the hand of their availability to learn and communicate at any time and in any place.